(untitled) (Global Journal of Science Frontier Research, 2016)
The quantitative and qualitative food loses and feed commodities is mainly done by insect pests which are prolific in nature and causes development of hot spots as a result of metabolic heat by developing insect populations, thereby create favorable conditions to various pathogens. Thus they cause two way spoilage of food commodities resulting into economic loss as well as loss to public health. Tribolium castaneum and Callasobruchus maculates are important pests on household material like wheat flour and Indian chick pea respectively. The essential oil of Rosemary Rosemarinus officinalis L. (Lamiales: Lamiaceae) has been investigated on toxicity of these pests under controlled conditions. The major compounds of the oil were analyzed by GC were as 1, 8 Cineol (20.021%), Borneol (7.17%), Camphor (6.541%), Geraniol (6.281%), Camphene (5.623%), Linalool (4.993%) Alpha fenchyl acetate (4.222%) and Verbenone (4.147%). Efficiency of Rosemary Oil was evaluated by various toxicity assays like Fumigant, Repellency, Contact and Ovicidal on both the pests simultaneously. The oil marked different activity against both of them.